Sealed with a hiss [large type] - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery, 2025)
"Spring is in full bloom, and everything is blossoming just right for Harry in Crozet, Virginia. Restorations to the long-shuttered local segregated school are nearly complete, and the school will be renamed to commemorate an important community member. To honor the former students, Harry and her friends are hard at work planning a reunion. It's a big affair, and the crew spends their days hanging plaques at the gym, arranging food, and writing speeches. But they come across something unexpected: a dead body. With a little aid from feline sleuths Mrs. Murphy and Pewter, Harry just might have a chance at solving this mystery."--